The basis of art appreciation / Noor Enfendi Desa, Syed Alwi Syed Abu Bakar and Noor A'yunni Muhamad - Desa, Noor Enfendi; Syed Abu Bakar, Syed Alwi; Muhamad, Noor A'yunni (Universiti Teknologi MARA, Perak, 2020)
This study revolves around identification of ways to observe or appreciate art since an artwork possesses its own aesthetic values which are related to a philosophy or an artist's cognitive style in conveying the meaning behind an artistic piece. According to Kamus Dewan Edisi Ke-4 (2007), aesthetic is one of the branches of philosophy that deals with the nature of beauty and taste, as well as the philosophy of art. In this research, the two main parts involved are the definition of terms and an analysis on artwork. Three components in definition of terms are describing art and style, art and idea, as well as art and context. Art criticism theory, introduced by Edmund Burke Feldman (1994) to interpret the meaning and context conveyed by an artist, is the method chosen for this study. Barret (1994) stated that art criticism is a response towards meaning and making a critical judgement on artworks. A piece of art has no value unless meaning is given to it (Ahmad Suhaimi & Jamilah, 2008).